(3ePcQGJ ef hQGA GdbHhQ (B:s (3GdLRA GdGhd (B: (3hbGFY eCSGI eHjJI (B/s - (3YaQhf, eMQRs ((3GdLRGFQ (B:s (3OGQ gheI ,s, 2008)
(3GdXQajI GdQGgfI ehGJjI dWQM GdehVhY ; Gf GdGQTja GdeQLYj GdNGU HEjGdI GdLRGFQ ef (B1789 (3Gdi (B1830 (3heG HYOgG dGjRGd MJi GdGf LRA eeG GSJMhPJ Ydjg aQfSG h JQaV GYGOJg ddLRGFQ, eeG LYd aQfSG Gdi cJGHI GdJGQjN MSH eG jNOe eUGdMgG(B... (3h jJYdb JCdja gPG GdcJGH dJMOjO ghjI GdaGYdjf aj GdeCSGI GdGSJYeGQjI h JhVjM OhQ cd hGMO efge s
Keywords: (3eCSGIs; (3hQGA GdbHhQs; (3aQfSGs; (3ePcQGJs